Diet composition and niche overlap of two sympatric carnivores: Asiatic jackal Canis aureus and Kashmir hill fox Vulpes vulpes griffithii, inhabiting Pir Lasura National Park, northeastern Himalayan region, Pakistan. Issue 1 (22nd February 2019) - Akrim, Faraz; Mahmood, Tariq; Nadeem, Muhammad Sajid; Dhendup, Tashi; Fatima, Hira; Andleeb, Shaista
Abstract : Studies on dietary habits and niche overlap of sympatric carnivore species can be vital for their conservation. They can reveal the potential level of inter‐specific competition and prey species overlap, thus highlighting species specific conservation requirements. We investigated diet composition of two such sympatric carnivore species Asiatic jackal Canis aureus and the Kashmir hill fox Vulpes vulpes grifithii in and around Pir Lasura National Park, in northeastern Himalayan region of Pakistan by using fecal analysis after confirming the carnivore species by genetic analyses. The scats of the two carnivores were collected during four different seasons of the year and analyzed in the laboratory. Results revealed sixteen prey species in the diet of Asiatic jackal and 21 species in the diet of the Kashmir hill fox. For Asiatic jackal, wild prey contributed approximately 18%, whereas 60% of the diet comprised of domestic prey. For Kashmir hill fox, the wild prey consumption was approximately 18%, while consumption of domestic prey was 51% and plants contributed 28%. Niche breadth of the Asiatic jackal was broader (0.78) compared to Kashmir hill fox (0.31). Niche overlap between these two sympatric carnivores was found to be a rather high 0.81.